Association of Macular Optical Coherence Tomography Measures and Deficits in Facial Recognition in Patients With Glaucoma - Khan, Sabine S. (JAMA Ophthalmol, 2021)
This study investigates the association between facial recognition and macular structural damage, as measured by spectral-domain ocular coherence tomography retinal ganglion cell and inner plexiform layer.